In vitro studies: The role of immunological cells in Indonesian thin tail sheep in the killing of the liver fluke, Fasciola - Estuningsih, S.E; Wiidjajanti, S; Partoutomo, S; ., Spithill; Raadsma, H; Piedrafita, D (Indonesian Journal of Animal and Veterinary Sciences, 2002)
Previous studies have shown that Indonesian Thin Tail (ET) sheep exhibit high resistance to challenge with Fasciola gigantica when compared with Merino sheep, and this resistance is expressed in early infection. In order to study the role of the immune system in this resistance to ET sheep, in vitro studies were undertaken in the laboratory. In vitro study to confirm the ability of immune cells from ET sheep in the killing of F. gigantica larvae has been done by incubating immune cells and F. gigantica larvae together with immune sera or normal sera. The viability of the larvae was observed over a period 3 days incubation by observing their motility. The results showed that the cells isolated from F. gigantica- challenged ET sheep in the presence of immune sera from ET were able to kill 70% of the larvae. In contrast, cells from infected Merino were unable to kill a significant number of F. gigantica using the same sera source. It seems that the cytotoxicity was dependent on the presence of immune sera and ET peritoneal cells, suggesting the potential role of an antibody-dependent cell cytotoxic (ADCC) mechanism in the resistant ET sheep. Key words: In vitro, Fasciola gigantica, peritoneal cell, sheep gigantica.